Palliative extubation: five-year experience in a pediatric hospital - Carolina de Araújo Affonseca; Luís Fernando Andrade de Carvalho; Renata de Pinho Barroso Quinet; Maíla Cristina da Cunha Guimarães; Verônica Ferreira Cury; Alexandre Tellechea Rotta (Elsevier, 2020)
Objective: To present the characteristics of pediatric patients with chronic and irreversible diseases submitted to palliative extubation. Method: This is a descriptive analysis of a series of patients admitted to a public pediatric hospital, with chronic and irreversible diseases, permanently dependent on ventilatory support, who underwent palliative extubation between April 2014 and May 2019. The following information was collected from the medical records: demographic data, diagnosis, duration and type of mechanical ventilation; date, time, and place of palliative extubation; medications used; symptoms observed; and hospital outcome. Results: A total of 19 patients with a mean age of 2.2 years were submitted to palliative extubation. 68.4% of extubations were performed in the ICU; 11 patients (57.9%) died in the hospital. The time between mechanical ventilation withdrawal and in-hospital death ranged from 15 minutes to five days. Thirteen patients used an orotracheal tube and the others used tracheostomy. The main symptoms were dyspnea and pain, and the main drugs used to control symptoms were opioids and benzodiazepines. Conclusions: It was not possible to identify predictors of in-hospital death after ventilatory support withdrawal. Palliative extubation requires specialized care, with the presence and availability of a multidisciplinary team with adequate training in symptom control and palliative care. Resumo: Objetivo: Apresentar as características de pacientes pediátricos portadores de doenças crônicas e irreversíveis submetidos a extubação paliativa. Método: Trata-se de análise descritiva de uma série de casos de pacientes internados em hospital público pediátrico, portadores de doenças crônicas e irreversíveis, dependentes de forma permanente de suporte ventilatório e que foram submetidos a extubação paliativa entre abril de 2014 e maio de 2019. Foram coletadas as seguintes informações do prontuário: dados demográficos, diagnóstico, duração e tipo de ventilação mecânica; data, hora e local de realização da extubação paliativa, medicamentos utilizados, sintomas observados e desfecho hospitalar. Resultados: 19 pacientes com idade média de 2,2 anos foram submetidos a extubação paliativa. 68,4% das extubações foram realizadas dentro da UTI, 11 pacientes (57,9%) evoluíram para óbito no hospital. O tempo entre a retirada de ventilação mecânica e o óbito hospitalar variou entre 15 minutos e 5 dias. 13 pacientes usavam tubo orotraqueal e os demais, traqueostomia. Os principais sintomas foram dispneia e dor e as principais drogas utilizadas para o controle dos sintomas foram os analgésicos opioides e benzodiazepínicos. Conclusões: Não foi possível identificar fatores preditores de óbito no hospital após a retirada do suporte ventilatório. A extubação paliativa demanda cuidado especializado com presença e disponibilidade de equipe multiprofissional com formação adequada em controle de sintomas e cuidados paliativos.